Metabolic Reliance on Photosynthesis Depends on Both Irradiance and Prey Availability in the Mixotrophic Ciliate, Strombidium cf. basimorphum - Hughes, Erin Ann; Maselli, Maira; Sørensen, Helle; Hansen, Per Juel (Frontiers in Microbiology, 2021)
Many species of the ciliate genus Strombidium can acquire functional chloroplasts from a wide range of algal prey and are thus classified as generalist non-constitutive mixotrophs. Little, however, is known about the influence of irradiance and prey availability on their ability to exploit the photosynthetic potential of the chloroplasts, and how this may explain their spatial and temporal distribution in nature. In this study, inorganic carbon uptake, growth, and ingestion rates were measured for S. cf. basimorphum under three different irradiances (10, 40, and 120 μmol photons m–2 s–1) when acclimated to three different prey densities (5×10^3, 1×10^4, and 4×10^4 cells mL-1), as well as when allowed to deplete the prey. After prey depletion, cultures survived without prey longest (~6 days) at the medium irradiance treatment (40 μmol photons m–2 s–1), while ciliate density, inorganic carbon uptake rates, and cellular chl-a content declined fastest at the highest irradiance treatment. This indicates that the ciliates may be unable to maintain the chloroplasts functionally without replacement at high irradiances. Ingestion rates were not shown to be significantly influenced by irradiance. The maximum gross growth efficiency (GGE) in this study (1.1) was measured in cultures exposed to the medium test irradiance and lowest prey density treatment (5×10^3 cells mL-1). The relative contribution of inorganic carbon uptake to the ciliate carbon budget was also highest in this treatment (42%). A secondary GGE peak (0.99) occurred when cultures were exposed to the highest test irradiance and the medium prey density. These and other results suggest that S. cf. basimorphum, and other generalist non-constitutive mixotrophs, can flexibly exploit many different environmental conditions across the globe.